2010
DOI: 10.1039/b925129d
|View full text |Cite
|
Sign up to set email alerts
|

Structural diversity in manganese, iron and cobalt complexes of the ditopic 1,2-bis(2,2′-bipyridyl-6-yl)ethyne ligand and observation of epoxidation and catalase activity of manganese compounds

Abstract: A ditopic 1,2-bis(2,2'-bipyridyl-6-yl)ethyne ligand, L, has been synthesized for the first time by consecutive Suzuki and Sonogashira coupling reactions either in a one- or two-step synthesis. Coordination of L with some first-row transition metals, Fe, Mn and Co showed a very rich structural diversity that can be obtained with this ligand. Reaction of L with Mn(II)(OAc)(2) yielded a dimanganese(II) complex, [Mn(2)L(mu-OAc)(3)]PF(6), (1) where the two somewhat inequivalent trigonal-bipyramidal Mn atoms separat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…[7] Metalation of L with Fe II (CF 3 SO 3 ) 2 ·4 MeCN yielded an orange crystalline compound [Fe II ( L )](H 2 O) 2 ](CF 3 SO 3 ) 2 ( 1 ), Figure 1. The crystal structure obtained is similar to an analogous [Fe II ( L )](SCN) 2 compound recently published.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[7] Metalation of L with Fe II (CF 3 SO 3 ) 2 ·4 MeCN yielded an orange crystalline compound [Fe II ( L )](H 2 O) 2 ](CF 3 SO 3 ) 2 ( 1 ), Figure 1. The crystal structure obtained is similar to an analogous [Fe II ( L )](SCN) 2 compound recently published.…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis of the catalyst precursor, Scheme , involved the preparation of 1,2‐bis(2,2′‐bipyridyl‐6‐yl)ethyne by reacting 6‐bromo‐2,2‐bipyridine with sodium acetylide through consecutive Suzuki and Sonogashira coupling reactions followed by hydrogenation over Pd/C to yield the tetradentate ligand, 1,2‐bis(2,2′‐bipyridyl‐6‐yl)ethane ( L ) . Metalation of L with Fe II (CF 3 SO 3 ) 2 ⋅ 4 MeCN yielded an orange crystalline compound [Fe II ( L )](H 2 O) 2 ](CF 3 SO 3 ) 2 ( 1 ), Figure .…”
Section: Resultsmentioning
confidence: 99%
“…33,34 Peracetic acid is used in the reaction with the dimeric Mn-catalyst 12, which quantitatively converts cyclooctene to the epoxide within 3 min (at 3 mol% catalyst loading, entry 12). 35…”
Section: Mirza Cokojamentioning
confidence: 99%
“…2). 32,35 Bhattacharyya et al reported the successful application of an ionic diperoxo tungsten complex, PPh 4 [WO(O 2 ) 2 (1-(2 0hydroxy-phenyl)ethanonoxime)] ( 13), in the epoxidation of 1-octene with H 2 O 2 . 36 A very low catalyst concentration (0.05 mol%) yields 95% 1-octene oxide within 2.25 h in acetonitrile at 40 1C.…”
Section: Mto (mentioning
confidence: 99%
“…The preparation of carboxylate-rich Mn complexes introduces synthetic complications, owing both to the kinetic lability of Mn(II) ions and the multiple binding modes of carboxylate ligands. 16,17 Significant problems include the generation of mono-, tri-, or polynuclear complexes, commonly encountered products in Mn-carboxylate chemistry. 18,19 Successful preparations of dinuclear Mn complexes with only carboxylate ligands and water molecules, rather than elaborate ligand moieties, have not yet been reported, indicating that the synthesis of dinuclear manganese complexes with O-rich coordination environments is a difficult task to achieve.…”
Section: Introductionmentioning
confidence: 99%